HIV/AIDS: medico legal issues / Nurjaanah Abdullah - Nurjaanah, Abdullah (1993)
"By the year 2000 AIDS could become the largest epidemic of the century, eclipsing the influenza scourge of 1918 .We are dealing with something that is expanding out of control."l Not only have medical and scientific researchers been frustrated by the mounting tragedy of their inability to discover effective treatments (let alone cure) for this "fiendishly fast-moving" disease, there also exists no definitive law(s) to cover all the possible legal issues that will be raised by it. Therefore, in this thesis it is only possible to explore the present situation and (hopefully) present tentative solutions to these problems. Chapter I gives a brief background and history of the Human Immunodeficiency Virus (HIV) and the Acquired Immunodeficiency Syndrome (AIDS) . This discussion is supplemented by data concerning HIV and AIDS to provide an overview of the urgency in respect of the current situation . Modes and implications of HIV transmission have also been included in this chapter. 1 "Invincible AIDS", Time Magazine, August 3, 1992, No. 31 at pp 17, 20. Chapter II focuses on the tests utilised by the National AIDS Reference Laboratory Enzyme-linked for detecting HIV-antibodies. These are the Immunosorbent Assay ( ELISA ) , particle agglutination and a supplementa latest . Consent for testing and the ongoing screening carried out under the Ministry of Health's Plan of Action for the Prevention and Control of AIDS are also elaborated . The impact of the medical and scientific tests defined in Chapter II are evaluated in Chapter III. In particular , the various legal consequences and implications of the test for HIV-antibodies based on such applicable laws as exist in Malaysia are highlighted. The major and broader areas touched upon are employment, confidentiality and insurance law . More specific issues such as those arising out of partner notification are dealt with in Chapter IV under negligence law, family law and criminal law. Chapter V describes and analyses the nature and application of criminal sanctions that may arise with references to HIV/AIDS cases. Euthanasia, suicide, murder and such defences as are available to these offences are particularly highlighted. More importantly , in this chapter , an attempt is made to evaluate the general rationale and primary purpose of the criminal law and its process . Questions as to its merits and justifications as an instrument of and for punishments in HIV/ AIDS situations are raised . A patient's right to refuse treatment is common l y recognised and acknowledged. However, when he exercises this right the medical practitioner and the health care team are l ikely to be placed in a difficult position. Chapter VI describes and outlines all the attendant problems t h a t may arise when this happens . Likewise, when the medical practitioner or a health care team refuses to treat a patient , similar difficulties are encountered . Ethical implications , criminal and civil liabilities and medical disciplina r y proceedings are explored and presented in Chapter VI. Various tentative conclusions and proposals are set out in Chapter VII under ( a) legislative intervention, (b ) judicial discretion and public policy and (c) extra-legal measures which include public education, supportive a ctions , good medical practice, family planning, programmes on s exually transmitted diseases , implications . pre- marriage test and human rights This thesis does not attempt to discuss in detail the complexities of Malaysian and common law as applicable to HIV/ AIDS situations . It only seeks to broadly appraise the present state of such laws as may likely affect the various parties in a HIV/AIDS dilemma.